Through A Glass Darkly: New Questions (And Answers) About IMF Programs - Joseph P. Joyce (Wellesley College, Department of Economics, 2002)
Recent research on the International Monetary Fund has focused on the adoption, implementation and impact of their lending programs and their political dimensions. This paper evaluates this literature and suggests promising areas of future work. The first area to be surveyed deals with the initiation of a Fund program, which has been shown to be influenced by political and institutional variables. The record also shows that in some cases governments borrow from the Fund on a continuing basis. A second focus of research analyzes the design and implementation of Fund supported polices, since many programs are often not successfully completed. Political economy models attribute the incomplete implementation to a lack of domestic support for reform measures, and empirical studies provide evidence is support of this hypothesis. The third issue that is addressed is the impact of IMF policies on the economy of the borrowing government. Most of the empirical work finds that these policies improve the balance of payments but may have a negative impact on growth and income distribution. Finally, there are no signs of a catalytic effect on Fund programs on private capital flows to program countries, but some evidence of moral hazard.
Keywords: F3; 330; Anpassungsprogramm des IWF; Zahlungsbilanz; Finanzmarkt; Moral Hazard; Welt